Author Correction: A study on the bio-applicability of aqueous-dispersed van der Waals 1-D material Nb2Se9 using poloxamer (Scientific Reports, (2021), 11, 1, (176), 10.1038/s41598-020-80730-2) - Chae, Sudong; Oh, Seungbae; Choi, Kyung Hwan; Lee, Jin Woong; Jeon, Jiho; Liu, Zhixiang; Wang, Cong; Lim, Changmo; Dong, Xue; Woo, Chaeheon; Asghar, Ghulam; Shi, Liyi; et al. (Scientific Reports, 2021)
This Article contains a typographical error in the Acknowledgements section. “This research was supported by Leading University Project for International Cooperation through the National Research Foundation of Korea (NRF) funded by the Ministry of Education (MOE) (NRF-2019R1F1A1063170); and partially supported by NRF-2019R1A2C1006972.” should read: “This research was supported by Leading University Project for International Cooperation through the National Research Foundation of Korea (NRF) funded by the Ministry of Education (MOE) (NRF-2019R1A2C2011563); and partially supported by NRF-2019R1A2C1006972”.